Thyroid hormones and female reproduction. Issue 5 (14th May 2018) - Silva, Juneo F; Ocarino, Natália M; Serakides, Rogéria
Abstract: Thyroid hormones are vital for the proper functioning of the female reproductive system, since they modulate the metabolism and development of ovarian, uterine, and placental tissues. Therefore, hypo- and hyperthyroidism may result in subfertility or infertility in both women and animals. Other well-documented sequelae of maternal thyroid dysfunctions include menstrual/estral irregularity, anovulation, abortion, preterm delivery, preeclampsia, intrauterine growth restriction, postpartum thyroiditis, and mental retardation in children. Several studies have been carried out involving prospective and retrospective studies of women with thyroid dysfunction, as well as in vivo and in vitro assays of hypo- and hyperthyroidism using experimental animal models and/or ovarian, uterine, and placental cell culture. These studies have sought to elucidate the mechanisms by which thyroid hormones influence reproduction to better understand the physiology of the reproductive system and to provide better therapeutic tools for reproductive dysfunctions that originate from thyroid dysfunctions. Therefore, this review aims to summarize and update the available information related to the role of thyroid hormones in the morphophysiology of the ovary, uterus, and placenta in women and animals and the effects of hypo- and hyperthyroidism on the female reproductive system. Abstract : Thyroid dysfunctions are associated with several morphophysiological and behavioral alterations, including reproductive disorders in women and animals. Thus, the objective of this review was to summarize the role of thyroid hormones in ovarian, uterine and placental morphophysiology.